Balinese Puppet Style As An Idea Of Ceramic Art Creation - I Wayan Mudra; I Gede Mugi Raharja; I Nyoman Wiwana; I Wayan Sukarya (Institut Seni Indonesia Denpasar, 2018)
Ceramic art products distributed in Indonesia are dominantly found as Chinese identity. This creation is aimed to create the art ceramics by Balinese style puppet ornaments. The creation method followed Gustamiâ€™s theory, namely exploration, improvisation, and embodiment. At the exploration stage, the data collection wasconducted through observation, interviews, and documentation. The design process was conducted in the improvisation stage, while the process of forming, burning, and finishing were conducted in the embodiment stage. The partners involved in this creation are UD Tri Surya Keramik and Bali Technology Center of Creative Ceramic Industry (BTIIK). The results of the creation show several works which have been created were inspired by the forms of potteries from Bali, Lombok, and Java which are marketed in Bali, namely sangku (rice bowl) and vase with various ornaments and sizes. This ceramic artwork was made using rotary technique and burned to a temperature of 1250oC. Balinese puppet style ornaments were applied using painting techniques.Produk Seni keramik yang dibuat dan dijual di Indonesia dominan ditemukan berindentitas Cina. Tujuan dari penelitian ini adalah untuk menciptakan produk seni keramik berornamen wayang style Bali. Metode penciptaan mengikuti teori Gustami, yaitu eksplorasi, improvisasi, dan perwujudan. Tahap eksplorasi, dilakukan pengumpulan data melalui observasi, wawancara, dan dokumentasi. Tahap improvisasi dilakukan proses desain dan pada tahap perwujudan dilakukan proses pembentukan, pembakaran dan finishing. Mitra yang dilibatkan dalam perwujudan adalah UD Tri Surya Keramik di Desa Kapal, Badung Bali dan Balai Teknologi Industri Kreatif Keramik (BTIKK) Bali. Hasil penciptaan menunjukkan beberapa karya seni keramik tercipta terinspirasi dari bentuk-bentuk gerabah Bali, Lombok, dan Jawa yang dipasarkan di Bali, seperti sangku dan guci. Karya seni keramik ini dibuat dengan teknik putar dan dibakar sampai mencapai suhu 1250oC. Karya seni keramik yang diciptakan berbentuk sangku dan guci dengan beberapa variasi ornamen dan ukuran. Wayang style Bali menjadi ornamen karya seni keramik ini, dibuat dengan teknik lukis.Â